Bacillus velezensis Isolate X5 Stimulates the Resistance of Resistant and Susceptible Banana Varieties to Foc Through Different Mechanisms - Yunlong Xu; Jun Wang; Guangxiang Tian; Changcong Liang; You Zhou; Lijia Guo; Yang Yang; Laying Yang (Journal of Fungi)
Banana wilt disease is an important disease in banana production, causing significant losses. Herein, we investigated the mechanism by which Bacillus velezensis isolate X5 enhances the resistance of different resistant banana cultivars to Fusarium oxysporum f. sp. cubense race 4 (Foc4). From the perspectives of metabolism, transcriptome, and key genes in important pathways, this study analyzed the composition and content changes of other types of signaling molecules, such as free amino acids and soluble sugars, in resistant/susceptible varieties. The results indicate that under pathogen stress, the contents of root-secreted metabolite components in both resistant and susceptible varieties increase significantly overall, and the increase in susceptible varieties is generally higher. For example, the free amino acid components in susceptible varieties are significantly more than those in resistant varieties. However, the addition of biocontrol bacteria can inhibit this increase. Exogenous addition experiments prove that differential metabolites can either promote or inhibit Foc4 and X5 at certain concentrations. The results of KEGG (Kyoto Encyclopedia of Genes and Genomes) enrichment and GO (Gene Ontology) annotation show that resistant varieties have more defense pathways compared to susceptible varieties. Under X5 treatment, more defense genes in resistant varieties are activated or their expression is enhanced, promoting the plant roots to secrete more substances related to plant resistance, such as phenylpropanoids and lignin. This research revealed the effects of Bacillus velezensis on bananas and pathogens, allowing valuable conclusions to be drawn. The results have good application potential to understand the relationships among the three species, defining the biocontrol effect and mechanism of Bacillus velezensis, and providing a theoretical basis for the biological control of soil-borne diseases such as banana wilt disease.